Consumer Preferences and Decision-Making in Digital Payments: A Systematic Review Using the Technology Acceptance Model (TAM) - Fadilah, Nuriya; Andriani, Nurita (PT FORMOSA CENDEKIA GLOBAL, 2025)
The development of digital technology has driven the adoption of digital payments such as e-wallets, mobile banking, and QRIS. This study employs a Systematic Literature Review (SLR) to analyze the factors influencing consumer preferences and decision-making based on the Technology Acceptance Model (TAM). The findings indicate that Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Use (ATU), and Behavioral Intention (BI) play a crucial role in the adoption of digital payments. Additionally, factors such as security, trust, economic incentives, and social influence also have a significant impact. Trust and security enhance user loyalty, while incentives and social influence accelerate adoption. Thus, while TAM remains relevant, external factors must be considered in the development of digital payment systems.